Preparation of Protective Structures for Use by People with Special Needs - Szmitkowski, Paweł (Roczniki Nauk Społecznych, 2025)
The aim of the article is to present a concise diagnosis of the system of protective structures in Poland and to propose a concept of adapting them to the requirements of people with special needs. It presents the shelter potential of our country and ways of ensuring that shelters are available. Attention was paid to the structure of shelters and rules for their occupancy. The conclusions proposed highlight the deficiencies in the legal basis for the preparation of protective structures in Poland, difficulties in adapting them, and the need to carry out systematic work, first covering facilities located near nursing homes or hospitals, and then other protective structures.